Komparasi Indeks Saham Syariah Indonesia (ISSI) Sebelum dan Saat Pandemi Covid-19 - Feren Anggun Pratitis; Taufiq Andre Setiyono (Journal of Islamic Economics and Finance, 2021)
Corona Virus Dieases 2019 (Covid-19) has become a global pandemic that has hit almost all countries. No exception, Indonesia is also the place where the epidemic has hit. Apart from the health sector, the economic sector is one of the sectors most affected as well. This can beseen in the country's economic recession and the decline in the stock price index. This research aims to determine the comparison of the Islamic stock index before and during the Covid-19 pandemic. Method this research is to use quantitative descriptive analysis method using paired sample t-test. The research was conducted from March 1, 2019 to March 1, 2021. The results showed that the increase in the number of Covid-19 cases did not significantly affect the movement of the Indonesian Sharia Stock Index (ISSI) so there was no significant difference between average prices. ISSI shares before and during the Covid-19 pandemic. With the results of this study, it is hoped that it can provide a reference for investors to choose and invest in Islamic stocks, because the strength of Islamic stocks is quite good.